Microstructure and Magneto-Dielectric Properties of the Chitosan/Gelatin-Yig Biocomposites - Casagrande-Denardin, J (2011)
This work is devoted to the preparation of yttrium iron garnet (YIG) ferrimagnetic biocomposites based in biodegradable chitosan and gelatin. The aim was to produce composite films containing controlled amounts of YIG to obtain a new biological material with magneto-dielectric features. Structural characterization of the biocomposites was made by scanning electron microscopy, X-ray diffraction, infrared absorption spectroscopy and thermal analysis, while the dielectric and magnetic properties were obtained from dielectric spectroscopy and magnetic hysteresis loops, respectively. The versatility of the films obtained makes them possible candidates for use as biomaterials or electronic device. © BME-PT.